Evaluation of ultrasonic scattering in agar-based phantoms using 3D printed scattering molds - Filippou, Antria; Damianou, Christakis A. (My University, 2022)
Purpose: Acoustic characterization of tissue mimicking materials in terms of attenuation, absorption, scattering and propagation velocity is essential for their utilisation in experiments, thus sparing the need for living tissues or cadavers. Although there is a vast literature regarding the acoustic characterization of such materials in terms of attenuation or propagation velocity, there is limited data regarding the quantification of the scattering coefficient. Herein stimulated the utilisation of four agar-based phantoms featuring different sizes of scattering agar-structures on one of their surfaces so as to provide experimental evaluation of the magnitude of scattering. Methods: The agar-based phantoms were developed with 6% w/v agar and 4% w/v silica and featured scatterers of sizes of 0–1 mm. The acoustic properties of propagation speed, impedance, insertion loss and attenuation were evaluated utilising the pulse-echo and through-transmission techniques. Scattering was deduced from the data. Results: The propagation speed measured at 2.7 MHz was in the range of 1531.23–1542.97 m/s. Respectively the attenuation as measured at 1.1 MHz was in the range of 1.216–1.546 dB/cm increasing with increased scatterer size. Respectively the scattering coefficient was in the range of 0.078–0.324 dB/cm. Moreover, the scattering coefficient was linearly dependent on frequency in the range of 0.8–2.1 MHz indicating a 6–23% effect of the total attenuation. Conclusions: The experimental results demonstrate the utilisation of the procedure for quantification of the scattering coefficient of tissue mimicking materials thus improving the diagnostic and therapeutic uses of ultrasound.
Keywords: Attenuation; Ultrasound; Scattering; Phantoms